Kinetic Modeling and Numerical Simulation as Tools to Scale Microalgae Cell Membrane Permeabilization by Means of Pulsed Electric Fields (PEF) From Lab to Pilot Plants - Knappert, Justus; McHardy, Christopher; Rauh, Cornelia (Frontiers in Bioengineering and Biotechnology, 2020)
Pulsed Electric Fields (PEF) is a promising technology for the gentle and energy efficient disruption of microalgae cells such as Chlorella vulgaris. The technology is based on the exposure of cells to a high voltage electric field, which causes the permeabilization of the cell membrane. Due to the dependency of the effective treatment conditions on the specific design of the treatment chamber, it is difficult to compare data obtained in different chambers or at different scales, e.g. lab or pilot scale. This problem can be overcome by the help of numerical simulation since it enables the accessibility to the local treatment conditions (electric field strength, temperature, flow field) inside a treatment chamber. To date, no kinetic models for the cell membrane permeabilization of microalgae are available what makes it difficult to decide if and in what extend local treatment conditions have an impact on the permeabilization. Therefore, a kinetic model for the perforation of microalgae cells of the specie Chlorella vulgaris was developed in the present work. The model describes the fraction of perforated cells as a function of the electric field strength, the temperature and the treatment time by using data obtained on a milliliter scale batchwise treatment chamber. Thereafter, the model was implemented in a CFD simulation of a pilot-scale continuous treatment chamber with colinear electrode arrangement. The numerical results were compared to experimental measurements of cell permeabilization in a similar continuous treatment chamber. The predicted values and the experimental data agreed reasonably well what demonstrates the validity of the proposed model. Therefore, it can be applied on any possible treatment chamber geometry and can be used as a tool for scaling cell disruption of microalgae by means of PEF from lab to pilot scale. This can help to develop new process and to decrease the cost for the development of new treatment chamber designs.